Effect Of Fused Deposition Modeling (FDM) Parameters On The Warpage And Different Composition Polylactic Acid/Ethylene-Vinyl Acetate Blend - Huan, Jia Yee (Universiti Sains Malaysia, 2022)
Fused Deposition Modelling (FDM) is a popular 3D printing method to create a part with complicated design and low cost. A common issue that occurs during FDM printing process is the warpage of the part which contributes to inadequate mechanical properties and reduced dimensional accuracy. This research aims to investigate the effect FDM processing parameters i.e bed temperature and printing speed on the warpage of printed parts produced from fabricated pure polylactic acid (PLA) and PLA/ethylene vinyl acetate (EVA) blend. The PLA/EVA blends were prepared by premixing using an internal mixing while filaments were fabricated using a single screw extruder. Study on the warpage of parts printed at different bed temperatures (50, 70 and 90°C) indicated that the warpage of pure PLA reduced with increasing bed temperature while a reverse trend was observed in blends due to a higher ability to crystallize in the former when printed at a higher temperature. Temperature at 50°C is considered the best bed temperature for reducing the warpage of the blends. Meanwhile, pure PLA and blends parts printed at different printing speeds (10, 35 and 70mm/s) indicated the lowest warpage when printed at 10mm/s. Comparison of tensile properties of compression moulded samples and samples produced from FDM showed similar reduction of tensile and modulus with increasing EVA content but lower values for 3D printed samples. However, 3D printed samples made from blends with 10wt% EVA in PLA indicated higher elongation at break compared with compression moulded samples suggesting better toughness of the former due to better interphase interaction between EVA and PLA.